Epigallocatechin gallate (EGCG) modification of structural and functional properties of whey protein isolate. (August 2022) - Han, Xiue; Liang, Zhiqiang; Tian, Songfan; Liu, Lu; Wang, Song
Graphical abstract: Highlights: Non-covalent and covalent interactions of EGCG with WPI have occurred. WPI and the resulting WPI-EGCG complexes were investigated. Changes in secondary structure of WPI-EGCG complexes were observed. Solubility, foaming and emulsifying properties of WPI-EGCG complexes were improved. Abstract: The objective of this paper was to investigate the interactions between (-)-Epigallocatechin-3-gallate (EGCG) and whey protein isolate (WPI) by covalent and non-covalent combinations and the effects of the interactions on the conformational and functional changes of whey protein. Conformational changes in the secondary structure of whey protein with various concentrations of EGCG were studied using FTIR spectra. EGCG was more likely to form covalent bonds than non-covalent bonds when it interacted with whey proteins. The addition of EGCG altered the conformation of whey protein. The content of β-sheet decreased, while that of β-turn increased, however, the random coil remained unchanged. An reduction in surface hydrophobicity was observed in all the WPI-EGCG complexes, suggesting that modification in secondary structure of WPI were induced by EGCG. Additionally, the emulsifying and foaming attributes of WPI were enhanced after interaction with EGCG. This study confirms that EGCG can enhance the functional properties of WPI. It is also a pointer to the possible application of WPI-EGCG complexes in the dairy industry.